EFEKTIVITAS KOMUNIKASI PENGGUNAAN APLIKASI ZOOMSEBAGAI MEDIA PEMBELAJARAN ONLINETERHADAP PRESTASI BELAJAR MAHASISWA ILMU KOMUNIKASI UNIVERSITAS RIAU SELAMA PANDEMI COVID-19 - Rola Julianda; Anuar Rasyid (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
The current Zoom application is not only a complement to the learning process, but has transformed into the best solution so that it can be said to be one of the needs for achieving effective learning during a pandemic like today. One of the academic activities of users of the Zoom Application is the University of Riau's Communication Studies Students Batch 2018, 2019, and 2020 who activelyuse the Zoom Application. According to CMC (Computer Mediated Communication) Theory, the CMC pattern allows a person to communicate using computer-based communication tools or gadgets supported by internet devices and applications that allow us to carry out various activities virtually such as discussing, reading, watching and accessing required sites. The method used in this research is to use quantitative research methods, and the type of research approach used is descriptive research. The data collection technique is an online questionnaire for Communication Studies Students at the University of Riau class, 2018, 2019 and 2020 as a research population with a total of 609 students and a sample of 85 students obtained through the slovin formula which is determined by purposive sampling technique and tested through the help of the SPSS application . The results of the research hypothesis using the "t test" the effect of communication effectiveness on learning achievement is 13.789 > 1.986. It is proven that tcount > ttable with a significance level of 5% with dk = n-2, then Ho is rejected and Ha is accepted. Shows that there is a significant influence between the effectiveness of communication on learning achievement in Communication Studies Students at the University of Riau during the Covid-19 pandemic. From the calculation results it can be concluded that there is an influence of X on Y by 68% with a fairly strong category. The results of the research on the effectiveness of communication using the Zoom application can be seen from 6 indicators according to Hardjana, namely indicators of receiver or user, message (content), time (timing), communication media (media), message (format), message source (source)